2012
DOI: 10.1080/00185868.2012.721699
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Citizenship Behavior and Work Experience

Abstract: The authors compared the relationship of elements of the Organizational Citizenship Behavior (OCB) and years of work experience of registered nurses in the state of Texas. Work experience research has shown a relationship between OCB and work experience through mediating roles of various work related characteristics does exist. Work experience is described as the overall length of time in an occupation or workforce. Civic virtue was the only element of organizational citizenship behavior to have a statisticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 22 publications
4
36
1
1
Order By: Relevance
“…Organisational citizenship behaviour can be promoted and developed by an organisation and its managers (Kegans et al., ). Concretely, five areas can be influenced by managers to increase OCB: high quality relationships, encouraging employees to recognize organisational justice and ethical climate, empowerment, recognition, and attraction and retention of staff.…”
Section: Practical Implications For Managersmentioning
confidence: 99%
See 3 more Smart Citations
“…Organisational citizenship behaviour can be promoted and developed by an organisation and its managers (Kegans et al., ). Concretely, five areas can be influenced by managers to increase OCB: high quality relationships, encouraging employees to recognize organisational justice and ethical climate, empowerment, recognition, and attraction and retention of staff.…”
Section: Practical Implications For Managersmentioning
confidence: 99%
“…Closely associated with age is the work experience of employees. Employees with long work experience are described as having high work-value congruence, which increases the possibility of promoting OCB; they are also described as participating more in civic virtue activities (Kegans, McCamey, & Hammond, 2012). As to gender, Bahrami et al (2013) showed that male employees in an Iranian teaching hospital demonstrated more OCB than their female counterparts.…”
Section: Individual Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…A moderation argument for work tenure was built, based on previous research showing that individual and contextual factors related to work experience bring valuable work-related skills, knowledge and incentives fostering individual and organizational outcomes (Lance et al, 1989;Ng and Feldman, 2010;Teskluk and Jacobs, 1988). In the current study, work experiences as number of years a person has been in a workforce or has been working was evaluated (Kegans et al, 2012;McDaniel et al, 1988) and intend to examine the degree to which work experience moderates the influence of LMX on OCB among higher-education lecturers.…”
Section: Introductionmentioning
confidence: 99%